Recent strategies for removal and degradation of persistent & toxic organochlorine pesticides using nanoparticles: A review. (1st April 2017) - Rani, Manviri; Shanker, Uma; Jassal, Vidhisha
Abstract: Organochlorines (OCs) are the most hazardous class of pesticides, therefore, banned or restricted in several countries. The major sources of OCs include food industries, agriculture and sewage wastes. Their effluents discharged into the water bodies contain extremely high concentration of OCs which ultimately causes environmental concern. Because of their high persistence, toxicity and potential to bioaccumulation, their removal from wastewater is imperative. The degradation techniques are now advanced using nanomaterials of various kinds. During the last few years, nanoparticles such as TiO2 and Fe are found to be excellent adsorbents and efficient photocatalysts for degrading more or less whole OCs as well as their toxic metabolites, which opens the opportunities for exploring various other nanoparticles as well. It is noteworthy that such methodologies are economic, fast and very efficient. In this review, the detailed information on different types of OC pesticides, their metabolites, environmental concern and present status on degradation methods using nanoparticles have been reviewed. An attempt has also been made to highlight the research gaps prevailing in the current research area. Graphical abstract: Highlights: Banned OCs pesticides residues in environment calls immediate elimination. Microorganisms-mediated-degradation of OCs is highly studied. TiO2 and zero-valent Fe nanoparticles are potential candidates in removal of OCs. Being efficient, nanomaterials have great opportunities in environment remediation. Details of OCs and their degradation using nanomaterials have been reviewed.